Mempelajari Pengaruh Konsentrasi Maltodekstrin dan Polivinil Pirolidon (PVP) terhadap Karakteristik Sifat Fisik Tablet Effervescent Kopi Robusta (Coffea robusta Lindl) - Lina Herlinawati (Ma'soem University, 2020)
Effervescent tablets are soft drink products that contain organic acids such as citric acid and sodium bicarbonate, which react quickly in water by releasing carbon dioxide. The purpose of this research is to increase the empowerment of coffee plants, namely Robusta coffee as a popular commodity, with Robusta coffee diversification into functional food products in the form of effervescent tablets. This study aims to determine whether there are variations in the concentration of maltodextrin and polyvinyl pyrrolidone (PVP) on the physical characteristics of robusta coffee effervescent tablets. The method / design used in this study is a Randomized Group Design pattern with each factor of three levels with three replications with variations in the addition of maltodextrin (10%, 15%, 20%) and PVP (2%, 3 %, 4%). The results showed that the concentration of maltodextrin as a filler had an effect on the physical response, namely hardness, dissolution time and weight uniformity of effervescent tablets of robusta coffee. Concentration of polyvinyl pyrrolidone (PVP) as a binder gives effect to the physical response, namely hardness and soluble time of effervescent tablets of robusta coffee. The interaction between maltodextrin concentration and polyvinyl pyrrolidone (PVP) concentration influences the physical response, namely hardness and soluble time of effervescent tablets of Robusta coffee. Based on the results of the study, the best treatment was obtained at 15% maltodextrin concentration and 4% PVP concentration.